Radiofrequency ablation in combination with CD73 inhibitor AB680 reduces tumor growth and enhances anti-tumor immunity in a syngeneic model of pancreatic ductal adenocarcinoma - Faraoni, Erika Y.; Strickland, Lincoln N.; O’Brien, Baylee J.; Barraza, Joseph F.; Thosani, Nirav C.; Wray, Curtis J.; Mills, Tingting W.; Bailey-Lundberg, Jennifer M. (Frontiers in Oncology, 2022)
Pancreatic ductal adenocarcinoma presents a 5-year overall survival rate of 11%, placing an imperative need for the discovery and application of innovative treatments. Radiofrequency ablation represents a promising therapy for PDA, as studies show it induces coagulative necrosis and a host adaptive immune response. In this work we evaluated the effects of RFA treatment in vivo by establishing a syngeneic mouse model of PDA and performing tumor ablation in one flank. Our studies revealed RFA acutely impaired PDA tumor growth; however, such effects were not sustained one week after treatment. Adenosine (ADO) pathway represents a strong immunosuppressive mechanism that was shown to play a role in PDA progression and preliminary data from ongoing clinical studies suggest ADO pathway inhibition may improve therapeutic outcomes. Thus, to investigate whether ADO generation may be involved in tumor growth relapse after RFA, we evaluated adenosine-monophosphate (AMP), ADO and inosine (INO) levels by HPLC and found they were acutely increased after treatment. Thus, we evaluated an in vivo CD73 inhibition in combination with RFA to study ADO pathway implication in RFA response. Results showed combination therapy of RFA and a CD73 small molecule inhibitor (AB680) in vivo promoted sustained tumor growth impairment up to 10 days after treatment as evidenced by increased necrosis and anti-tumor immunity, suggesting RFA in combination with CD73 inhibitors may improve PDA patient response.